Cerita Rakyat Tokoh Gayatri Rajapatni sebagai Sarana Penguatan Profil Pelajar Pancasila Pada Siswa SMA - Achmad Ichsan Arpriansyah; Titik Dwi Ramthi Hakim (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2022)
Folklore is a variety of literary works that existed earlier than other literary works. Folklore developed from generation to generation. It can be from old stories to fibers or chronicles written by ancient masters or writers. The figure of Gayatri Rajapatni himself is the daughter of King Kertanegara of the Singosari Kingdom. The leadership of the Majapahit government at that time, Gayatri had the right to rule. In fact Gayatri chose to become a royal advisor. Character formation in students can be developed through the material in the learning process. It was Gayatri's figure that made the second era after Raden Wijaya a great empire because he had an agile and intelligent regent for his upbringing. The intelligent, feminine, and nationalist character of Gayatri Rajapatni can be used as character teaching materials by students. This study aims to introduce and utilize local folklore as a form of character education for students. Researchers used a qualitative descriptive approach by using literature review techniques. Researchers get data from the results of previous research collections, the youtube platform, and so on.